The Relationship between the Transformational Leadership Style of Madrasah Head and Work Discipline with the Performance of Teachers at MTsN Lima Puluh Batu Bara - Muhammad; Rahmat Hidayat (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
This study aims to determine the magnitude of the relationship between the leadership style of madrasa principals and work discipline with the performance of teachers in MTsN Lima Puluh Batu Bara District. The sample of this research was determined by 42 people (total sampling). The data collection tool used a Likert scale questionnaire. The questionnaire was arranged based on variable indicators and examined by the Thesis Advisor, then tested on respondents who were not research samples. After testing the instrument, it is known that all X1 instruments consisted of 37 valid items 21 items, variable X2 consisted of 26 valid items 24 items and Y consisted of 40 valid items 24 items. Test requirements for data analysis of variables X1, X2 and Y are known that all variables are normally distributed, so that linearity testing and linearity test results can be found, it turns out that the regression between variables X1 with Y and X2 with Y is also linear with p values ​​<0.05. Shows that: First, the transformational leadership style of madrasa principals is positively and significantly related to the performance of teachers in MTsN Lima Puluh Batu Bara District. In the research hypothesis test, obtained correlation X1 with Y of 0.379. Second, work discipline is positively and significantly related to teacher performance in MTsN Lima Puluh Batu Bara District. In the research hypothesis test, obtained correlation X2 with Y of 0.374. Third, the madrasa head transformational leadership style and work discipline together are positively and significantly related to the performance of teachers in MTsN Lima Puluh Madrasah, Batu Bara District. In the research hypothesis test, obtained correlation X1 and X2 together with Y of 0.554.